PENINGAKATAN HASIL BELAJAR BAHASA INDONESIA DENGAN MENGGUNAKAN MEDIA WAYANG KARTUN MATERI ASAL USUL KELAS IV C SD NEGERI 007 SAMARINDA ULU - Safira Trian Nisa; Muhlis; Hety Diana Septika; ⁠⁠Sukriadi; Ilham Abu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Student learning outcomes in the Indonesian language subject at SD Negeri 007 Samarinda Ulu are still relatively low because learning is dominated by conventional methods. Teachers rely more on lecturing and make little use of engaging media, causing students to become passive. This condition affects the achievement of learning outcomes, which have not yet met the Minimum Mastery Criteria (KKTP) of 75. Therefore, innovation through interactive and enjoyable learning media is needed. Cartoon puppet media was chosen because it can present material visually and concretely, as well as facilitate students’ understanding of the story content. This study aims to improve the Indonesian language learning outcomes of grade IV C students through the use of cartoon puppet media in the topic of origin stories. The research employed Classroom Action Research (CAR), carried out in two cycles. Each cycle consisted of the stages of planning, implementation, observation, and reflection. The research subjects were 27 grade IV C students of SD Negeri 007 Samarinda Ulu in the 2024/2025 academic year. Data were collected through observation, learning outcome tests, and documentation, while analysis was conducted descriptively and quantitatively by calculating the mean score and the percentage of student mastery. The results showed an increase in learning outcomes after the application of cartoon puppet media. In the first cycle, the average student score was 68.80 with 62% mastery, while in the second cycle it increased to 81.90 with 86% mastery. In addition, student activity also improved, as seen from higher participation, the ability to answer questions, and the confidence to express opinions.